2020
DOI: 10.1186/s12887-020-02382-5
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of intellectual disability in individuals from special education schools in the south of Brazil

Abstract: Background Intellectual Disability (ID) is characterized by significant limitations that affect intellectual functioning, adaptive behavior, and practical skills which directly interfere with interpersonal relationships and the environment. In Western countries, individuals with ID are overrepresented in the health system, often due to associated comorbidities, and its life-time cost places ID as one of the most expensive conditions of all diagnoses in the International Classification of Diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Our study cohort, similar to other SOI games worldwide, was predominantly male (Gothwal et al 2017;Special Olympics Health 2018;Woodhouse et al 2004). This is understandable given that males experience higher rates of Down syndrome, autism spectrum disorder, and ID disorders with X-linked inheritance, with about one-third of X-linked ID syndromes associated with ocular abnormalities (Couser et al 2017;Oliveira et al 2020). Our study also found females to have a higher likelihood of reporting eye complaints, specifically headache, and of having tropia on distant and near cover tests.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our study cohort, similar to other SOI games worldwide, was predominantly male (Gothwal et al 2017;Special Olympics Health 2018;Woodhouse et al 2004). This is understandable given that males experience higher rates of Down syndrome, autism spectrum disorder, and ID disorders with X-linked inheritance, with about one-third of X-linked ID syndromes associated with ocular abnormalities (Couser et al 2017;Oliveira et al 2020). Our study also found females to have a higher likelihood of reporting eye complaints, specifically headache, and of having tropia on distant and near cover tests.…”
Section: Discussionsupporting
confidence: 51%
“…2017; Oliveira et al . 2020). Our study also found females to have a higher likelihood of reporting eye complaints, specifically headache, and of having tropia on distant and near cover tests.…”
Section: Discussionmentioning
confidence: 99%
“…Both autism and ID are complex neurodevelopmental conditions with chromosomal, monogenic, and polygenic causes with many proposed risk genes (Yin et al, 2020). Children with developmental regression may have associated genetic, metabolic or environmental causes identified (Oliveira et al, 2020). Approximately 30% of autistic children have co‐occurring ID or global developmental delay (GDD) (Shenouda et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…ID is an etiologically diverse condition [ 5 , 6 ], and the specific causes are often difficult to identify. Underlying biological, genetic, and neurological factors are most likely to be identified in persons with severe to profound ID, and they are responsible for even up to 75% of such cases [ 7 , 8 ]. Determining the etiology of MID is more difficult as it has a multifactorial origin consisting of a diverse set of factors, not limited solely to biology and genetics [ 2 ].…”
Section: Introductionmentioning
confidence: 99%